Influence Of Accreditation Readiness In Improving The Quality Of Teacher Teaching In PAUD Banguntapan Bantul Subdistrict - Hibana, Hibana; Surahman, Susilo (Universitas Negeri Semarang, 2021)
Recognition of educational institutions is demonstrated through accreditation and quality of teaching. This research aims to explain the influence of PAUD accreditation readiness on the quality of teaching in 40 PAUDs in Banguntapan. Research methodology uses quantitative descriptive. The results showed the existence of six criteria for the willingness of accreditation mechanisms that must be met, among others: first, general requirements; Second, special requirements; third, classification of accreditation applications; fourth, the completeness of the document; fifth, validation and verification; and sixth, accreditation results. The results showed X2h>X2t, where there was a significant influence on accreditation readiness to the quality of teaching in PAUD Banguntapan. Meanwhile, six schools focus on general requirements, and six schools also on specific needs. Twelve schools prepare for the early stages of the school's survival. Furthermore, eight schools in the preparation stage of accreditation application classification; seven schools in the readiness stage of the process and awaiting visit; ten schools in terms of validation and verification; And three schools are fully prepared for accreditation.